Optimizations of Hydroxyl Terminated Polymerization of Mannose Tricyclic Orthoester Toward Ready-to-use Lipomannan Backbone - Harin Leelayuwapan (Science Faculty of Chiang Mai University, 2019)
Throughout the life cycle of mycobacterium tuberculosis (Mtb), its survival critically depends on its interactions with mammalian host cells. Therefore, in order to have better treatments for and preventions of tuberculosis (TB), it is important to understand the biological activity of the Mtb surface components. a-1,6 Polymannan, the backbone of lipomannan (LM), is present abundantly on the surface of mycobacterium tuberculosis and interacts with mammalian hosts. Conjugation of polymannan with thiol linker comprises an essential biochemical tool to study the Mtb surface interactions with mammalian hosts. A short alkyl chain with hydroxyl head group is employed to attach to the reducing end of the polysaccharide via a glycosidic bond, and with a terminal thiol group to serve as a linker. The target - conjugated polymannan with thiol linker is achieved by a rapid synthetic route, relying on a ring-opening polymerization, using a tricyclic mannosyl orthoester as monomer. The ring-opening polymerization, triggered by a Lewis acid without the presence of the linker, was previously proposed to be terminated by water at the reducing end. However, in the present study, the results suggest that the polymerization may also be initiated from the reducing end by the attack of the hydroxyl head group of a short chain alkyl thiol linker. After that, an elongation of the growing polysaccharide may be achieved via the propagation to the non-reducing end. Optimizations for the polymerization and termination in a one-pot reaction were carried out. A half gram of the synthetic target molecule is attained in a single chemical step. The target synthetic bacterial surface molecule is in a ready-to-use form to be utilized further in several applications, such as immobilization on surfaces and conjugation to carrier proteins for biological and immunological studies. This biochemical tool may lead us to a better understanding on carbohydrate-based biointerfaces between the bacteria pathogen and the human immune system.